A MODEL SUGGESTION FOR BUDGETING ACTIVITY COST REDUCTION UNDER ACTIVITY BASED KAIZEN BUDGETING APPROACH - Pazarceviren, Selim Yuksel; Akcin, Olcay; Ozsuer, Ugur (European Scientific Journal, ESJ, 2015)
Nowadays, competitive global business life surrounds various companies around the world. Production technology develops in a very fast manner. Also, companies are in need of advanced budgeting and costing techniques in order to make more profit and stand strong in this fast changing scene. Companies use Activity Based Budgeting (ABB), Activity Based Costing (ABC), and Activity Based Management (ABM) systems to gain successful results. These systems concentrate on overhead costs in order to assign real production cost. In this study, we consider activity based systems and introduce a new model to apply Kaizen Budgeting through ABB and ABC approach in a business organization. Also, we aim to illustrate a case study for an activity center in order to explain our kaizen budgeting model. Our ABB and ABC model has been used in many organizations in Turkey and its success has been proved for years ago. However, our new model will be the first approach for ABB and ABC model via kaizen budgeting. We aim to reduce the organization’s variable cost by kaizen budgeting in an efficient manner. Furthermore, we classified costs into four categories such as resource costs on the basis of the volume of activities, resource costs on the basis of activity level, resource costs independent from the volume of activities, and direct resource cost. This approach enables us to reduce the variable costs of activities according to their characteristics.